MOBILE BANKING DALAM CASHLESS SOCIETY MENUJU BNI DIGITAL BANKING - Adhitya Nandha Karuniawan; Edy Swasono; Ahsin Daroini (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Technological developments have changed people’s way of life to be cashless based. The establishment of a cashless society led BNI to develop their identity as a digital banking. BNI Mobile Banking has become an example. This research was discussed with qualitative methods with in-depth interviews with seven research informants. Depend on three functions of BNI Mobile Banking, there was information, communication, and transaction, it can be concluded that BNI Mobile Banking being an application as one door service owned by BNI. An example is cash withdrawal without using debit card named BNI Mobile Tunai. Through BNI Mobile Banking, public can find out various information about BNI. So, the rejuvenation of BNI Mobile Banking becomes the face of BNI as a financial institution that can create brand image of BNI and public perception. The digital perception and novelty possessed by BNI Mobile Banking as a face of BNI forms customer loyalty which references BNI to others and show invulnerability to other banking applications.